KAJIAN EFEKTIFITAS PENGGUNAAN BERBAGAI JENIS PIPA PADA BANGUNAN RUMAH TINGGAL BERDASARKAN PEMODELAN INSTALASI PIPA AIR BERSIH DAN ANALISIS ANGGARAN PELAKSANAAN - Dedi Budi Setiawan; Rifqi Aulia Abdillah; Supriyo Supriyo; Arief Subakti Ariyanto; Hadi Wibowo (Politeknik Negeri Semarang, 2022)
The installation of clean water is a very important building component to supportthe activities of residents in the building, because this component is a provider ofwater needs for building occupants to carry out bathing, washing, cooking activities,and so on. In planning a clean water installation system, four criteria must be met,namely: Sufficient quantity, Hygienic, Optimal technical, and Economical. Researchhas been carried out by modeling clean water installation to determine the type ofpipe that most effectively meets the clean water installation criteria to be applied toresidential buildings. The method used in this study is the modeling of a clean waterpipe installation with 3 types of pipes (Polyvinyl Chloride (PVC), Poly PropyleneRandom (PPR), and Galvanis), measuring the flow rate and water pressure bysimulating all the open sanitation points and simulating one of the open sanitationpoints in turn, then performing calculation of Implementation of Budget Plan forpipe installation. The results showed that the flow rate and pressure readings on thePVC pipe installation experienced an increase in the flow rate of 0.00624 m3 andthe pressure decreased by 3.015 psi, the PPR pipe installation experienced anincrease in the flow rate of 0.0104 m3 and the pressure decreased by 3.86 psi, whilethe galvanized pipe installation experienced an increase in the flow rate of 0.029 m3and the pressure decreased by 3,285 psi. The cost needed to make a PVC pipeinstallation is Rp. 336,635, to make a PPR pipe installation of Rp. 514,583, and toinstall a Galvanized pipe of Rp. 538,370. Based on the results of testing and analysisof the implementation budget, it can be concluded that the most effective type of pipeto be used in the installation of clean water pipes in residential homes is PVC pipe.